Imipramine-induced immunomodulation and intracellular growth inhibition during Brucella abortus 544 infection in RAW 264.7 cells and BALB/c mice - Aguilar, Ched Nicole Turbela; Huy, Tran Xuan Ngoc; Nguyen, Trang Thi; Salad, Said Abdi; Cho, Seong Eun; Hong, Il-Hwa; Min, Wongi; Lee, Hu Jang; Kim, Suk (Frontiers in Veterinary Science, 2025)
Brucellosis is a significant zoonotic infection with increasing global prevalence. Traditional treatments rely on antibiotic combinations, but challenges such as drug resistance and relapse necessitate the exploration of alternative therapeutic options. Imipramine hydrochloride (ImiP) has shown potential as an adjunctive treatment for infectious diseases. This study investigates the immunomodulatory effects of ImiP in B. abortus 544 infections in murine macrophages and BALB/c mice. In vitro, RAW 264.7 cells exposed to ImiP exhibited reduced B. abortus replication, decreased nitrite levels, and enhanced bactericidal effects. In vivo, ImiP treatment significantly decreased bacterial loads in the spleen (10 mg/kg, **p < 0.01; 20 mg/kg, *p < 0.05) and liver (10 mg/kg, **p < 0.01; 20 mg/kg, ***p < 0.001), compared to untreated controls. Histopathological analysis revealed minimal liver microgranuloma formation and periportal inflammation in ImiP-treated mice. Moreover, flow cytometry showed decreased CD4+ and CD8+ T cell expression, while serum cytokine profiling indicated a Th1-driven immune response, characterized by elevated levels of IL-12 and decreased IL-10. These findings suggest that ImiP possesses both immunomodulatory and antibacterial effects, highlighting its potential as an adjunctive therapy for brucellosis.